2019
DOI: 10.1186/s12906-019-2709-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the Cucurbitacins, a novel class of small-molecule inhibitors of Tropomyosin receptor kinase a

Abstract: BackgroundNGF-TrkA is well known to play a key role in propagating and sustaining pruritogenic signals, which form the pathology of chronic pruritus. Inhibition of NGF-TrkA is a known strategy for the treatment of pruritus. In the present paper, we describe the identification, in vitro characterization, structure–activity analysis, and inhibitory evaluation of a novel TrkA inhibitory scaffold exemplified by Cucurbitacins (Cus).MethodsCus were identified as TrkA inhibitors in a large-scale kinase library screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Tropomyosin receptor kinase A (TrkA) is a surface transmembrane tyrosine kinase serving as a receptor for NGF and contributes to the development of psoriasis and pruritic response [196]. NGF stimulates histamine secretion from mast cells and sensitization of peripheral sensory nerve terminals.…”
Section: Tropomyosin-receptor Kinase a Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tropomyosin receptor kinase A (TrkA) is a surface transmembrane tyrosine kinase serving as a receptor for NGF and contributes to the development of psoriasis and pruritic response [196]. NGF stimulates histamine secretion from mast cells and sensitization of peripheral sensory nerve terminals.…”
Section: Tropomyosin-receptor Kinase a Inhibitorsmentioning
confidence: 99%
“…Conversely, another study (n = 208) among psoriatic patients reported clinical improvement in terms of psoriatic lesions but no significant reduction of itch when compared with vehicle (4.2 points according to WI-NRS vs. 3.9 points; p = 0.362) [198]. Recently, Zhong et al [196] explored the inhibitory properties against the NGF/TrkA pathway of cucurbitacins, which are tetracyclic triterpenes derived from plants (especially the Cucurbitaceae family). The authors implied cucurbitacins could be potential precursors of successful antipruritics in the future.…”
Section: Tropomyosin-receptor Kinase a Inhibitorsmentioning
confidence: 99%